Analisis Harga Pokok Produksi Pada Usaha Mebel Sinar Harapan Di Kecamatan Tallunglipu Kabupaten Toraja Utara - Richard Loloran Langkun; Agustinus Mantong; Helba Rundupadang (Jurnal Manajemen dan Ekonomi Kreatif, 2023)
This study aims to analyze the cost of goods produced by Sinar Harapan's mebel business. Determining the cost of goods produced is very important because it further increases competition that occurs between companies in producing quality products at fairly competitive prices. This research was conducted at Mebel Sinar Harapan Business, a business that produces various types of furniture made of wood. The analysis method used is descriptive quantitative data collected by documentation method which is then analyzed with descriptive analysis techniques with a quantitative approach. Data analysis techniques use the full costing method by calculating raw material costs, labor costs, and factory overhead costs. Based on the results of the study, it can be concluded that the calculation of cost of goods produced as a basis for determining selling prices according to the full costing method is better in analyzing production costs.